COVID -19 and pregnancy: epidemiology and clinical evolution - Vigil-De Gracia, Paulino; Cabrera, Carlos; Faneite, Pedro; Cuadra, Cesar; Rivero Fraute, Alexandra (Gaceta Médica de Caracas, 2021)
The relationship of COVID-19 and pregnancy implies a novel clinical condition, information regarding the true medical picture is currently being collected. The present work aims to carry out a review of the most prominent publications on COVID-19 and Pregnancy: epidemiology and clinical evolution based on currently available evidence.